Medicines adherence in children - Aldosari, Mohammed (2021)
Poor medicines adherence in children is one of the common problems in the health care system. Knowing the medicines adherence rate in individual children is important to understand the consequences of non-adherence. Different factors can contribute to poor adherence such as forgetting, lack of understanding about the treatment or disease, age of child, socioeconomic status, medicines schedule and taste. Strategies that target these factors may improve medicines adherence. This research explores methods of measuring medicines adherence and the barriers and facilitators to medicines adherence in children with diverse diseases. A systematic review of measures of medicines adherence in children was conducted. Six databases were searched to identify studies published in the last ten years and therefore to focus on the methods recently used to assess medicines adherence in children. Inclusion criteria were original research studies measuring medicines adherence in children. Only 31 articles met the inclusion criteria and were included. The review identified seven methods which had been used to measure adherence; self-report, Electronic Monitoring Devices (EMD), dose count, canister weight, plasma level, checking medical records or pharmacy refill data, and contact by mobile phone. Currently, no gold standard method to measure adherence to medicines in children exists as each method has its own advantages and disadvantages.